Language mixing of a Bangla-English learning bilingual child - Parveen, Shapla; Ahamad Shah, Mohamed Ismail (2015)
The present study investigates the mixed utterances produced by a mono-ethnic simultaneous bilingual child receiving Bangla and English as his two first languages, a phenomenon referred to as Bilingual First Language Acquisition (BFLA). The form and structural patterns of the mixed utterances produced by the bilingual child with both his Bangla and English speaking caregivers are explored. This investigation examines three months of naturalistic data which has been extracted from a longitudinal research from the age of two years till the child attained the age of two years eight months. The data reveals that Bangla was the child’s dominant language at that stage which is also explicit in the Mean Length of Utterance (MLU) count. There is evidence of both “intra-” and “inter-” utterance language mixing with a greater proportion of such cases with the English speaking interlocutor than with the Bangla speaking interlocutor. The relationship between parental input and the child’s output is discussed focusing on lexical and grammatical categories present in the corpus of the child’s mixed utterances. The study also discusses whether parental strategies have an influence on the child’s language choices and mixed utterances and examines whether there are more significant factors other than parental strategies, such as typological differences between the two languages, which may have led to cross-linguistic influences affecting the child’s language mixing patterns.